PENERAPAN STRATEGI PEMBELAJARAN EVERYONE IS A TEACHER HERE DALAM MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 004 HIDUP BARU KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Susi Susanti; Eddy Noviana; Guslinda Guslinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: the problem in this research is the lack of active involvement of students both in the ability to listen, argue, ask questions, communicate among others, discussion and attitude of responsibility between individual students so students are unable to express their opinions in front of the class and students do not master how to make questions and answer the question well. This study aims to determine the differences in student social studies learning outcomes and how much the increase in social studies learning outcomes of third grade students of SDN 004 Hidup Baru Kampar Kiri Tengan District, Kampar Regency between before and after the application of learning strategies everyone is a teacher here. This research method uses an experimental method with one group pretest-posttest research design. Data on social studies learning outcomes in this study were collected using a technique in the form of objective tests. The results of this study indicate that there are differences in social studies learning outcomes of third grade students of SD Negeri 004 Hidup Baru Kampar Kiri Tengan District, Kampar District between the pretest and posttest data. This can be seen from the initial test average of 57.68 to 81.25 with an increase in learning outcomes of 0.54 which is included in the medium interpretation. Based on the results of the analysis, it was concluded that the learning strategies of everyone is a teacher here can improve social studies learning outcomes of students in Class III 004 SDN Hidup Baru The District Of Kampar Kiri Tengah The Regency Of Kampar.Key Words: Learning strategies everyone is a teacher here, social studies learning outcomes